Dielectric relaxator behaviour of the system Sr1-xLaxTi1-xCoxO3 (x ≤ 0.40) - Parkash O.; Prasad Ch.D.; Kumar D. (My University, 2025)
The dielectric behaviour of the valence-compensated solid solution Sr1-xLaxTi1-xCoxO3 (x=0.05, 0.10, 0.20, 0.30 and 0.40) has been studied as a function of temperature and frequency. Compositions with x=0.20, 0.30 and 0.40 exhibit high values of dielectric constant. This high dielectric constant is due partly to the presence of interfacial polarization, and partly to the formation of grain-boundary barrier layers in these materials. The presence of barrier layers is shown by complex plane impedance analysis. © 1990 Chapman and Hall Ltd.